STRATEGIES FOR ENHANCING SPEAKING PROFICIENCY THROUGH INDONESIAN CULTURE IN ILFL CLASSES - Riani, Asma; Syafryadin (SEAMEO QITEP in Language, 2025)
ABSTRACT This study examines strategies for improving speaking proficiency in Indonesian Language for Foreign Learners (ILFL) through culturally integrated instruction. Using qualitative data from interviews with 15 learners and 10 instructors, five key strategies were identified: task-based learning, cultural immersion, peer interaction, constructive feedback, and multimedia use. These methods provide learners with real-life contexts, reduce speaking anxiety, and build confidence. Cultural immersion, in particular, enhances learners’ understanding of Indonesian society and supports meaningful communication. Peer activities promote collaboration and fluency, while multimedia resources expose learners to natural speech and varied accents. The findings confirm the value of integrating cultural content into ILFL teaching practices. This study recommends incorporating these strategies into ILFL curriculum and teacher training programs to foster both linguistic and intercultural competence among learners.